Weather shocks, prices and productivity: Evidence from staples in Mexico - Jesus Arellano Gonzalez; Miriam Juarez-Torres; Francisco Zazueta Borboa (Banco de México, 2023)
In this paper, we investigate the effect of weather shocks on the price of two crops of great importance in Mexican agriculture: white corn and dry beans. We rely on panel data techniques applied to a 20-year long panel of prices at the market/city level. Our results show that positive temperature and negative precipitation shocks of at least 0.5 standard deviations relative to the climate normal have immediate and lagged positive effects on the price of these crops. The immediate effect is about 2.0%, while the lagged effect is between 1.0% and 2.5%, depending on the timing of the shock within the crop's growing period. We also show that one of the mechanisms explaining the effect of weather shocks on the price of these crops is their detrimental effect on productivity, especially for rainfed production.
Keywords: E31; Q15; Q54; 330; Food Inflation; Weather Shocks; Staple Prices; Local Markets